Euroskepticism in the Crisis: More Mood than Economy - Jo Ritzen; Klaus F. Zimmermann; Caroline Wehner (Institute for the Study of Labor (IZA), 2014)
Before the Great Recession, rising income inequality within the European Union member states has been considered to be one driver for an increasing Euroskepticism. Using rich data on attitudes towards European integration from the Eurobarometer (EB) surveys, we revisit the issue by analyzing the relation between macroeconomic indicators, socio-economic background variables, individual attitudes and the level of Euroskepticism within the 27 EU member states for the period 2006 to 2011. Our analysis shows that Euroskepticism has increased by on third during the financial crisis, while income inequality on average stayed stable. We find that the increase in Euroskepticism is mostly due to mood: the fear of losing cultural identity and financial expectations and by large unrelated to economic background variables like income inequality. We find evidence that negative financial expectations are positively related to Euroskepticism in Western European countries and negatively related to Euroskepticism in Eastern European countries. That suggests that financially pessimistic people in Western Europe might interpret European integration as a threat to their financial situation, while Eastern European people might view it as a chance to improve their economic situation.
Keywords: D31; J31; O43; O52; P48; Z18; 330; Euroskepticism; income inequality; expectations; economic growth; unemployment